P.021 Esophageal cooling for hypoxic ischemic encephalopathy: a feasibility study. (5th June 2019) - Smith, T; Couillard, P; Hruska, P; McBeth, P; Kortbeek, J
Abstract : Background: Targeted temperature management (TTM) is a recognized treatment to decrease mortality and improve neurological functionin hypoxic ischemic encephalopathy (HIE). An esophageal cooling device (ECD) has been studied in animal models but human data is limited. ECD appear to offer similar benefits to intravascular cooling catheters with potentially less risk to the patient. We studied whether the ECD could act as a substitute for intravascular cooling catheters.Methods: Eight ICU patients admitted following cardiac arrest who required TTM were enrolled prospectively. The primary outcome measures were timeliness of insertion, ease of insertion, user Likert ratings, time to achieve a target temperature of 36˚C and time target temperature was maintained within 0.5˚C of the 36˚C goal for 24 hours using an ECD.Results: Time to reach target temperature 0 min to 540 min. ECD appeared to be effective at maintaining a target temperature of 36˚C for most patients. In general, the catheter was easy to insert and use.Conclusions: For patients requiring TTM, use of an ECDadequately allowed for TTM goalsto be achieved and maintained. Overall user evaluationwas positive.